Estimation of Crop Water Requirement of Pineapple (Ananas comosus (L.) Merr.) for Drip Fertigation - S. R, Maneesha; Desai, Sujeet; Devi, S.Priya; Gupta, Mathala J. (International Journal of Bio-resource and Stress Management, 2022)
The experiment was conducted at the research farm of ICAR- Central Coastal Agricultural Research Institute, Goa, India during 2016–2019 to estimate the crop water requirement (CWR) of pineapple during different growth stages and compare the pineapple crop performance and economic viability at different irrigation systems. Crop water requirement of pineapple was calculated based on the consolidated weather data of 14 years and crop evapotranspiration (ETc) of pineapple at different growth stages using Penman-Montieth equation using CROPWAT 8.0 software. In the experiemtal location, maximum crop evapotranspiration was found in the month of May (81 mm month-1) and the minimum was in the month of July (25 mm month-1). Crop water requirement was the highest in April (0.67 litre day-1 plant-1). During the period of monsoon, irrigation was withdrawn due to sufficienct soil moisture situation. Performance of pineapple crop under different systems of irrigation viz., surface irrigation, drip irrigation and drip fertigation was studied and found that the highest plant height (76.90 cm), D leaf width (5.45 cm), number of leaves (43), D leaf weight (150.3 g) and fruit weight (2.35 kg) were in drip fertigation. An estimated yield of 96.80 t ha-1 was recorded under drip fertigation treatment followed by drip irrigation (90.99 t ha-1) and surface irrigation (76.45 t ha-1) treatments. The cost economics analysis of pineapple production under different treatments revealed that the highest gross returns (` 14.5 lakhs), net returns (` 7.9 lakhs) and B:C ratio (1.2) were in drip fertigation treatment. Adoption of drip fertigation system in pineapple crop under west coast agro-climatic conditions of Goa is helpful to enhance the crop growth and yield of pineapple and fetch good economic returns.